Antibiotics and their environmental implications - Zirena Vilca, Franz (2018)
Due to its extensive use in various livestock production activities and its use in human health care, antibiotics have become an environmental problem that draws the attention of the scientific community. Several research works report their presence in different ecosystems compartments, as well as their impact in organisms that inhabit these ecosystems which are being investigated by this community; until now, it has been reported problems of bacterial resistance and damages at DNA level in living beings, among others; in this perspective it is necessary to perform monitoring in various environmental matrixes, in order to detect and quantify their presence, to have a better understanding of their long-term effects on living beings. In this sense, it addresses aspects that determine their presence in the ecosystem, as well as shows results of works evaluating their removal of contaminated water, in order to ensure their safety from an environmental perspective and taking into consideration the health of living beings and human beings.